Pocket radar guide key radar facts, equations, and data - Curry, G. Richard (SciTech Publishing, 2010)
The book covers the following topics about radar concept; frequency; antennas; transmitters; receivers and signal processor; waveforms; radar cross-section; radar equation; detection and search; measurement and tracking; clutter; atmosphere, rain and ionosphere; decibels (dB), and list of symbols.